CD147 and the EGFR Signaling Cascade in Head and Neck Cancer. (23rd August 2013) - Frederick, John W.; Sweeny, Larissa; Hartman, Yolanda; Rosenthal, Eben L.
Abstract : Objectives: Establish the relationship between two membrane bound proteins, CD147 and epidermal growth factor receptor (EGFR), through cutaneous squamous cell carcinoma (cSCC) cell lines. Methods: A pre‐clinical investigation using three cSCC cell lines (Colo‐16, SRB‐1, and SRB‐12) that were treated in vitro with a range of chimeric anti‐CD147 mAb (0, 50, 100, 200 µg/mL) or transfected with a small interfering RNA against CD147 (SiCD147). Cell proliferation, migration, and protein expression was then assessed. PCR analysis and immunofluorescent staining were also obtained. In vivo, Colo‐16 xenografts were treated with anti‐CD147 mAb (200µg i.p. triweekly), and tumors were then harvested for histologic analysis. Results: In response to anti‐CD147 treatments there was a significant decrease in cell proliferation ( P <.05) and migration in vitro ( P <. 001). These findings were confirmed with a Colo‐16 SiCD147 cell line. Western blot analysis showed a decrease in not only CD147 expression but also the EGFR signaling cascade, specifically EGFR, BAD, and AKT. EGFR mRNA expression was decreased on PCR analysis in response to anti‐CD147. In vivo response to anti‐CD147 showed decreased tumor growth and, on histologic analysis, decreased CD147 and EGFR expression. Conclusions: Blocking CD147 inhibits cell growth in vitro and in vivo and results in downregulation of EGFR expression and signaling cascades. CD147 could be exploited as a therapeutic target in cSCC by modulation of the EGFR signaling pathway.